Indicadores de Eutrofização na Represa Billings, São Paulo: Apoio ao Planejamento Urbano e à Gestão de Mananciais - Santos, Fabiano Sampaio Rodrigues dos; Ribeiro, Andreza Portella; Oliveira, Anderson de; Gallego, Jorge L (National Journal of City Management, 2025)
Objective: To assess water quality in the Billings Reservoir by calculating the Trophic State Index (TSI) using total phosphorus (TP) and chlorophyll-a (Chl-a) as indicators, in order to support urban planning and water resource management in the Metropolitan Region of São Paulo.Methodology: Analysis of secondary data from CETESB (2020-2022) for 9 monitoring stations regarding indicator quantification in samples collected during dry and rainy seasons. The relationship between TP and Chl-a was assessed through statistical inference tests, controlling for spatial variability among sampling sites. TSI was calculated according to Lamparelli's (2004) methodology, and results were spatially distributed in thematic maps using QGIS software.Originality/Relevance: The study provides an updated diagnosis of one of Brazil's most important water sources, supplying approximately 21 million inhabitants, while contextualizing institutional and socioeconomic constraints that hinder water resource management in the Metropolitan Region of São Paulo.Results: The reservoir exhibited predominantly supereutrophic and hypereutrophic conditions, with maximum TP and Chl-a concentrations of 510 µg/L and 511 µg/L, respectively, exceeding by up to 51 times the limits established by CONAMA Resolution 357/2005. ANCOVA confirmed that TP is the predominant factor in Chl-a variation (F=30.65; p
Keywords: Eutrophication; Water Quality; Billings Reservoir